Obtenção regiosseletiva de 5-alquil(aril/heteroaril)-3- (carboxil/trifluormetil)-1h-1-fenilpirazóis - Correa, Michele Stach (2011)
This paper presents a new synthetic route for obtain regioselective 5-alkyl(aryl/heteroaryl)-3-trifluoromethyl-1H-1-phenylpyrazoles (3a-e) (50-85% yields) and 5-alkyl(aryl/heteroaryl)-3-carboxialkyl-1H-1-phenylpyrazoles (4a-e) (51-89% yields) via cyclocondensation reactions of the type [3 + 2], using 1,1,1-trifluoro(chloro)-4-alkyl(aryl/heteroaryl)-4-alkoxy-3-alken-2-ones as 1,3-dielectrophile blocks and 1-phenylsemicarbazide as a new 1,2-dinucleophile. Compounds (3a-e, 4a-e) were synthesized by reactions between 4-alkoxy-1,1,1-trifluoro(chloro)-3-alken-2-ones (1a-e, 2a-e) and 1- phenylsemicarbazide in molar ratio 1:1.5, respectively, conducted in methanol as solvent and sulfuric acid as catalyst, at temperature of 60 °C and with a reaction time of 24 hours. The developed synthetic method enables the achievement of the regioselective 1,3-substituted pyrazole as a single product and/or majority in a single step reaction through the hydrolysis of the amide group. Also, the conversion of the trichloromethyl substituent, present in the precursors (2a-e), in a carboxyalkyl group was successful overcome. Finally, two series of 5-(alkyl/aryl)-4-bromo-3-(carboxyl/trifluoromethyl)-1H-1-phenylpyrazoles (7a-c, 8a-c) were obtained starting from the reactions of synthesized pyrazoles (3a-b,3e, 4a-b,4d) with N-bromosuccinimide in N,N-dimethylformamide (DMF) as solvent, in a temperature of 80 °C and with a reaction time of 2 hours (35-82% yields).